Children's Mental Health over the Early Life Course: The Impact of Economic Resources, Neighborhood Disorder, and Family Processes - Comeau, Jinette M (2015)
Drawing upon a stress process and life course framework, and using data from the Child Supplement of the National Longitudinal Survey of Youth, the three papers presented in this dissertation examine the extent to which economic resources, neighborhood disorder, and family processes influence children’s trajectories of mental health. In the first paper, I empirically construct six categories that represent children with comparable profiles of family income over time: increasing, decreasing, fluctuating, and stability across low-, medium-, and high-income families. The income categories are incorporated in multiple group latent growth curve models to assess the extent to which they initiate and shape children’s mental health trajectories from age 4 to 14. Results reveal significant disparities in antisocial behavior and depression/anxiety at age 4 and over time across the income categories. In the second paper, I use these income categories to examine how stability and change in family income influences trajectories of maternal emotional support and the provision of cognitive stimulation in children’s home environments. In subsequent analyses, I examine the extent to which these different economic profiles moderate the relationship between family processes and children’s mental health trajectories. In the third and final paper, I examine the relationship between stability and change in perceived neighborhood disorder and children’s trajectories of mental health. I conceptualize perceived neighborhood disorder as a two-part process involving a binary component that distinguishes between children exposed to minimal vs. high levels of disorder, and a continuous component that represents the actual level of disorder for children in the latter category. These two processes capture stability and change in neighborhood disorder over time, and are included in parallel process latent growth models to examine their separate and distinct impact on children’s trajectories of mental health. The results from these papers underscore that the duration and sequencing of socioeconomic status, both at the family and neighborhood level, have important implications for children’s mental health and family processes. The results also underscore the complex and dynamic ways family processes influence children’s mental health in different economic contexts